The digestibility of biofloc meal from African catfish culture medium as a feed raw material for Pacific white shrimp - Julie Ekasari; Muhammad Agus Suprayudi; Putri Elas; Reza Karunia Senja (Jurnal Akuakultur Indonesia)
ABSTRACT